AN EXPLORATORY QUALITATIVE STUDY OF COMPETITIVE STRATEGIES USED BY SMALL AND MEDIUM-SIZED ENTERPRISES IN BOTSWANA - Govender, Krishna K; Naude, Micheline; Munodawafa, Tadios (Universitas Nusa Cendana, 2025)
The study explored factors impacting the sustainable competitive advantage of small and medium-sized manufacturing enterprises (SMEs) in Botswana. Through face-to-face interviews, primary data were collected from a purposively selected sample of seven key government informants. Thematic analysis was used to analyze the data. The main findings revealed that manufacturing enterprises in Botswana are affected by high rentals and high costs of land (space), equipment, and product quality. SMEs that export their products face additional challenges of traceability issues and mileage charges in the countries where they export their products. The study recommends that funding organizations should continue to review collateral issues to increase access to finance for SMEs. The Botswana government and tribal authorities issuing land should remove bottlenecks related to the application for land, especially for business purposes. Access to water should also be reviewed to simplify the application process for water rights, especially for youth-funded ventures. The government should continue to promote joint ventures between multinational corporations because such efforts result in the transfer of funds, technology, and skills. Government subsidies should be offered for SMEs which incur significant mileage costs when they export their products to foreign markets. Manufacturing SMEs should also consider SME equity funding as an alternative to funding, and offer less risk compared to commercial banks and existing government-sponsored funding agencies. The findings of the study contribute towards the development of a sustainable theoretical framework that can be used by manufacturing SMEs to identify and utilize their internal resources and capabilities to increase their competitiveness and survive. The findings may also help to identify additional intervention strategies for manufacturing SMEs by the Botswana government and other stakeholders from both the public and private sectors. Keywords: SMEs; Manufacturing Enterprises; Sustained Competitive Advantage; Developing Economies